Role of brain nitric oxide in the thermoregulation of broiler chicks - Coleone, A. C. [UNESP]; Torres, K. A. A. [UNESP]; Carnio, E. C.; Gargaglioni, L. H. [UNESP]; Macari, Marcos [UNESP]; Furlan, Renato Luis [UNESP]; Bicego, K. C. [UNESP] (Elsevier B.V., 2009)
Nitric oxide (NO) plays a key role in body temperature (Tb) regulation of mammals, acting on the brain to stimulate heat loss. Regarding birds, the putative participation of NO in the maintenance of Tb in thermoneutrality or during heat stress and the site of its action (periphery or brain) is unknown. Thus, we tested if NO participates in the maintenance of chicks' Tb in those conditions. We investigated the effect of intramuscular (im; 25, 50, 100 mg/kg) or intracerebroventricular (icv; 22.5, 45, 90, 180 mu g/animal) injections of the non selective NO synthase inhibitor L-NAME on Tb of 5-day-old chicks at thermoneutral zone (TNZ; 31-32 degrees C) and under heat stress (37 degrees C for 5-6 h). We also verified plasma and diencephalic nitrite/nitrate levels in non-injected chicks under both conditions. At TNZ, 100 mg/kg (im) or 45,90,180 mu g (icv) of L-NAME decreased Tb. A significant correlation between Tb and diencephalic, but not plasma, nitrite/nitrate levels was observed. Heat stress-induced hyperthermia was inhibited by all tested doses of L-NAME (im and icv). Tb was correlated neither with plasma nor with diencephalic nitrite/nitrate levels during heat stress. These results indicate the involvement of brain NO in the maintenance of Tb of chicks, an opposite action of that observed in mammals, and may modulate hyperthermia. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Central nervous system; Heat stress; L-NAME; Nitrite; Nitrate